SOSIALISASI SEX EDUCATION PADA ANAK DI SDN 1 MOJOWARNO JOMBANG - Peni Haryanti; Diastuti, Indah Mei; Hidayati, Athi’; Aziz , Abd. (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2022)
The high number of cases of violence against children in Indonesia, especially in Jombang Regency, has become the main topic in the community and has even become a national news headline. Sexual violence against children is often carried out by those closest to them, so it is difficult for children to fight back. Even children are afraid to report this, one of the reasons is the lack of acceptable sex received by children. The role of the closest people, especially parents and teachers, is needed to teach sex education so that it is not a taboo topic in society. So that if a case occurs, it will be detected earlier and handled faster. The implementation of community service activities carried out by lecturers and students of the University of Hasyim Asy'ari Tebuireng Jombang with the title